2018
DOI: 10.1007/s10340-018-0976-y
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling pest infestation and biological control in low-input orchards: the case of apple blossom weevil

Abstract: Low input farming is an alternative production system that provides a great opportunity to disentangle the natural mechanisms regulating crop pests, since neither pests nor their natural enemies are disrupted by pesticides. Here we use a key apple pest in Europe, the apple blossom weevil (Anthonomus pomorum), as a model case to unravel the factors driving pest infestation and its biological control in a low input context, namely the cider apple orchards of NW Spain. We applied a holistic approach based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
(90 reference statements)
0
4
0
1
Order By: Relevance
“…2017). Another article presented evidence for birds as a promising alternative to pesticides for controlling weevils (Miñarro & García 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2017). Another article presented evidence for birds as a promising alternative to pesticides for controlling weevils (Miñarro & García 2018).…”
Section: Resultsmentioning
confidence: 99%
“…One article found that the use of natural enemies, specifically raptors predating on vole populations, was as effective as rodenticide use with the added benefit of reduced costs for the farmer (Machar et al 2017). Another article presented evidence for birds as a promising alternative to pesticides for controlling weevils (Miñarro & Garc ıa 2018).…”
Section: Evidence Of Disservicesmentioning
confidence: 99%
“…This analysis was carried out in the three main maize growing areas in Spain: the northeast (Catalonia and Aragón), central Spain (Madrid and Castilla-La Mancha) and the southwest (Extremadura and Andalusia). Also, Miñarro and García (2018) carried out a comparative study distributed over a 600 km 2 area in Asturias, to determine the factors driving pest infestation, in which three of the orchards were organic, one applied the broad-spectrum insecticide Lambdacyhalothrin and the rest followed IPM guidelines. Additionally, Sánchez-Moreno et al (2018), assessed the effects of organic farming with Bacillus thuringiensis on pest control, soil diversity and functioning in Castilla La Mancha.…”
Section: Insecticidesmentioning
confidence: 99%
“…Zabrodina et al (2020) call the apple blossom weevil “one of the most harmful insects in horticulture” and report yield losses for Russia and the Ukraine of 50–100 %. The increasing pest status of A. pomorum poses a serious threat to organic apple orchards and integrated pest management (IPM) systems currently in use in European apple orchards ( Miñarro & García, 2018 ; Shaw, Nagy & Fountain, 2021 ).…”
Section: Introductionmentioning
confidence: 99%